Estudio de factibilidad para la creación de una Unidad Educativa Particular en el cantón Quinsaloma provincia de Los Ríos, a partir del periodo lectivo 2014-2015 - Poveda Barahona, Jaime Daniel (2013)
The development of the present Feasibility Study for opening of an Individual Educational Unit in Quinsaloma Canton of Los Ríos Province, seeks to assess the main aspects in the administrative, financial, technical, economic and legal to implement the project. To satisfy in a better way the needs of the population has designed an organization established with an adequate logistical and technological support, complete with spacious classrooms equipped with innovated secure office furniture all under efficient management, solidarity and fraternity, which fostering a genuine pedagogical innovation reflected in an excellent quality of education, consolidation of ethical, moral, social and spiritual. The market analysis developed, allowed a vision acceptance of service that aims to achieve the project through an analysis of supply and demand, thus allowing estimations of the same, resulting in the Canton Quinsaloma by its economic, social and business is shown as an excellent place for the opening of the Educational Establishment. The initial investment required for the implementation of the project is $ 111.533,67. According to market research, technical, economic and financial the project is feasible, because it reflects the following values: a rate of return (IRR), attractive enough 25%, when compared to the minimum acceptable rate of return (MARR) that according to the calculations is 20,63%. A Net Present Value (NPV), indicates that the project will generate a wealth of $ 13.560,32 over the life of a Cost Benefit, indicating project is profitable because it has a cost benefit ratio (RB/C) of $ 1,17, which means that for every dollar invested investors get $ 0,17 long-term recovery, a recovery period of investment (PRI ) 4 years, 9 months and 10 days and a balance of $ 141.835,58.